Adopsi Inovasi PTT pada Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) Padi di Kecamatan Sukawati, Kabupaten Gianyar - N. Dewi Maryani; N. Suparta; IG. Setiawan AP (JURNAL MANAJEMEN AGRIBISNIS, 2014)
Innovation PTT consists of 12 components that can be recommended to improve rice yields and production efficiency by taking into account the input of natural resources wisely . The purpose of this study is (1) To describe the behavior of farmers and the rate of adoption of innovation PTT, (2) to analyze the influence of the characteristics of farmers, extension workers and the nature of innovation competence PTT on farmer behavior , (3) to analyze the influence of the characteristics of farmers, extension workers and the nature of innovation competence PTT the adoption of PTT innovation, and (4) to analyze the influence of behavioral factors on the adoption of PTT in District Sukawati innovation . The population in this study were all farmers who have followed the SL - PTT program in 2012 in the district of Sukawati. The number of samples in this study were 157 farmer respondents, obtained from 10 % of the population with proportional  Random sampling method. The types of data collected in this study is qualitative and quantitative data . Data analysis used descriptive analysis and statistical analysis with analysis tools Partial Least Square ( PLS ) Visual 1.04bl version . The results showed that (1) The behavior of farmers and the rate of innovation adoption of PTT in the District of Sukawati were high, (2) Characteristics of farmers, extension workers and the nature of innovation competence significantly affect farmers behavior, (3) The nature of innovation significantly affect innovation adoption PTT, while the characteristics of farmers and extension workers competence did not significantly affect the adoption of PTT innovation , and (4) The behavior of farmers significantly affect innovation adoption of PTT in District Sukawati . PTT Innovation Adoption in District Sukawati only influenced by the nature and behavior of innovation PTT farmers. Advice can be given is (1) The intensity of assistance that are applicable extension needs to be improved so as to fix the application of skills and legowo row planting method, fertilizer N based on leaf color chart, pest and disease control with crop rotation and the use of biological pesticides by farmers; (2) Extension should pay attention and use the properties of PTT innovation in assisting the farmers, and; (3) There needs to be a model and other studies with different variables.